POTENSI NAGARI KATAPIANG SEBAGAI DESTINASI WISATA DI KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Putri, Viorgi Dwi; Kasmita, Kasmita; Pramudia, Heru (Journal of Home Economics and Tourism, 2017)
The purpose of research is to determine the potential of Nagari Katapiang as aTourist Destination. This research consists of four indicators of Tourist Destinatiosare: attractions, accessibility, amenities, and ancellary service. This type of researchis descriptive research using qualitative approach method. Sampling technique isPurposive sampling. Data were collected by observation, interview, anddocumentation involving 13 informants. the results of the research, researchers foundsome potential that is (1) Natural attractions: the dragon fruit gardens, watermelongardens, Panjang beach and karambia ampek beach. (2) Cultural attractions: maelopukek, ulek ambek, randai, batagak gala panghulu, sate lokan, gulaikapalo lauak, juskarambia mudo. (3) Nagari Katapiang has amenities: toilets, mushalla, drinkingplaces, and lodges established at the edge of Pantai Katapiang. However, the area ofnagari Katapiang does not yet have accommodation. There is also no ancellaryservice.Keywords: Tourist potential, and Tourist Destination.